2006
DOI: 10.1073/pnas.0603057103
|View full text |Cite
|
Sign up to set email alerts
|

Androgen receptor as a licensing factor for DNA replication in androgen-sensitive prostate cancer cells

Abstract: Androgen receptor (AR) protein expression and function are critical for survival and proliferation of androgen-sensitive (AS) prostate cancer cells. Besides its ability to function as a transcription factor, experimental observations suggest that AR becomes a licensing factor for DNA replication in AS prostate cancer cells and thus must be degraded during each cell cycle in these cells to allow reinitiation of DNA replication in the next cell cycle. This possibility was tested by using the AS human prostate ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
116
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 122 publications
(123 citation statements)
references
References 32 publications
7
116
0
Order By: Relevance
“…This finding also supports and explains a recent finding that AR functions similar to a licensing factor. 24 The bidirectional effect of AR on MCM7 in LNCaP and PC3 cells with forced expression of AR is consistent with previous findings that a low dosage of androgen induces cell proliferation, whereas a high dosage induces cell growth arrest. 3 It appears that at a high dosage of testosterone, the cell .…”
Section: Discussionsupporting
confidence: 79%
“…This finding also supports and explains a recent finding that AR functions similar to a licensing factor. 24 The bidirectional effect of AR on MCM7 in LNCaP and PC3 cells with forced expression of AR is consistent with previous findings that a low dosage of androgen induces cell proliferation, whereas a high dosage induces cell growth arrest. 3 It appears that at a high dosage of testosterone, the cell .…”
Section: Discussionsupporting
confidence: 79%
“…These results together with the blockade of cellcycle progression at S phase by ERRb suggest that ERRb may arrest the proliferating cells at G 0 /G 1 phase. Intriguingly, AR also demonstrates a downregulation or degradation pattern during mitosis in androgen-sensitive prostate cancer cells (Litvinov et al, 2006). Besides its well-characterized roles in regulation of prostatic cell growth and differentiation via regulation of its target genes, AR is also shown to play a novel role in DNA replication in prostate cancer cells via a mechanism of forming pre-replicative complexes with some transcriptional co-regulatory proteins at DNA replication foci and such complexes become degraded during mitosis by a proteasome-dependent pathway, thus restricting only one round of DNA replication per cell cycle (Sharma et al, 2003;Huang et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…38 Lastly, it was recently shown that AR is degraded in mitosis; although this latter observation was reported to suggest a putative "licensing" function for AR in controlling DNA replication, this concept has yet to be tested. 39,40 Taken together, it appears that AR principally drives cell cycle progression through modulation of the G 1 -S transition, and that substantive lines of cross-communication between AR and the cell cycle machinery ultimately contribute to the mitogenic action of androgen.…”
Section: Ar-mediated Cell Cycle Progressionmentioning
confidence: 99%